2021
DOI: 10.3389/fmolb.2021.747601
|View full text |Cite
|
Sign up to set email alerts
|

Osh6 Revisited: Control of PS Transport by the Concerted Actions of PI4P and Sac1 Phosphatase

Abstract: Osh6, a member of the oxysterol-binding protein–related protein (ORP) family, is a lipid transport protein that is involved in the transport of phosphatidylserine (PS) between the endoplasmic reticulum (ER) and the plasma membrane (PM). We used a biophysical approach to characterize its transport mechanism in detail. We examined the transport of all potential ligands of Osh6. PI4P and PS are the best described lipid cargo molecules; in addition, we showed that PIP2 can be transported by Osh6 as well. So far, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 43 publications
2
12
1
1
Order By: Relevance
“…Our results make perfect sense in the light of recent, elegant in vitro experiments with Osh6p in artificial membranes (Eisenreichova et al, 2021). Here, the ORD domain was shown to have exceptionally high affinity for PI4P, such that it actually inhibited binding and transport of the counter lipid, PS.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our results make perfect sense in the light of recent, elegant in vitro experiments with Osh6p in artificial membranes (Eisenreichova et al, 2021). Here, the ORD domain was shown to have exceptionally high affinity for PI4P, such that it actually inhibited binding and transport of the counter lipid, PS.…”
Section: Discussionsupporting
confidence: 64%
“…A number of scenarios could be envisioned that may preclude productive transfer of PM PI4P to mitochondria by ORP5 ∆TMD -FKBP. One possibility is suggested by recent studies of the homologous yeast protein, Osh6p (Eisenreichova et al, 2021). That study reported that binding of PI4P by Osh6p is so tight that lipid transfer is actually inhibited.…”
Section: Resultsmentioning
confidence: 99%
“…Several scenarios could be envisioned that may preclude productive transfer of PM PI4P to mitochondria by ORP5 ∆TMD -FKBP. One possibility is suggested by recent studies of the homologous yeast protein, Osh6p (Eisenreichova et al, 2021). That study reported that binding of PI4P by Osh6p is so tight that lipid transfer is inhibited.…”
Section: Resultsmentioning
confidence: 99%
“…And if PI4P can be presented to and hydrolyzed by SAC1 mito , why isn’t PI4P transfer to the mitochondrial outer membrane not normally observed? A clue comes from elegant in vitro work on Osh6 and ORP8 (Eisenreichova et al, 2021; Ikhlef et al, 2021); here, the ORD domain was shown to have exceptionally high affinity for PI4P, such that it inhibited binding and transport of the counter lipid, PS. These experiments predicted and demonstrated a requirement for PI4P hydrolysis for PS transport to occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation